Public Trust in Public Institutions in Sarawak / Kuldip Singh, Arenawati Sehat Haji Omar and Zalina Mohd Desa - Singh, Kuldip; Haji Omar, Arenawati Sehat; Mohd Desa, Zalina (2021)
Concerns for restoring citizens’ trust in government are at the core of public sector modernization. Public distrust is often blamed on the bad functioning of public services, and in political discourse well-functioning, public services are said to create trust in government. Concern with low levels of trust in government and the negative image of government and the public administration has stimulated Western governments to engage in a modernization strategy for their public service. Public trust refers to the situation where public organizations are competent, open, and honest, characterized by concern for stakeholders and response to them, and identified with public goals, norms, and values (Shockley-Zalabak et al., 2003). In other words, from the organizational perspective, public trust can be defined as a relationship reflecting the degree to which all stakeholders trust the organization's competencies, organizational goals, shared standards and values, organizational principles, processes, procedures, codes of conduct, and care for internal and external stakeholders. Intra- organizational trust relates to individuals employed in an organization or to a system that is that organization. Trust in the organization includes positive expectations for other members of the organization, groups, and the organization. It is more than cumulative trust in each number of relationships. It also includes relationships between people and structures, as well as mechanisms for shaping organizational behaviors (Adams et al., 2008).